Implementasi Strategi Problem Solving dalam Pembelajaran PAI pada Kelas XI IPA di SMA Al-Washliyah 1 Medan - Arlina, Arlina; Hasibuan, Darma Syahputra; Amanda, Della Latifah; Nanda Ayuningtyas (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The aim of this research is to apply problem solving strategies in PAI learning in class XI Science at SMA Al-Washliyah 1 Medan. This research uses qualitative research methods, with data collection techniques in the form of observation, interviews and documentation used to collect and strengthen research data. The research subjects were students of class XI Science at SMA Al-Washliyah 1 Medan. With data validity techniques in the form of lingering and lengthy, as well as triangulation. The research results showed that the implementation of problem solving strategies in PAI learning in class